Geospatial data assimilation and mapping groundwater vulnerability in high plains aquifer using DRASTIC Model - Datta, Sumon; Ajaz, Ali (Fundamental and Applied Agriculture, 2019)
High Plains Aquifer is one of the most important aquifers in the United States, accounting for one-fourth of total annual freshwater withdrawal, and one-fifth of crop production of some major crops. But the area above this aquifer has not been extensively researched for determining the risk of groundwater pollution. Therefore, this study was undertaken to determine the groundwater pollution potential using the DRASTIC model in a Geo- graphic Information System (GIS) environment. Despite the limited data availability, DRASTIC model proved effective in delineating areas of High Plains Aquifer susceptible to groundwater contamination. The results from the model indicated that large portions of southwestern Texas, central Kansas, eastern Colorado, eastern Wyoming, western and north-western Nebraska were highly vulnerable to groundwater pollution whereas Oklahoma had the lowest vulnerability.